Proximate Composition of Seed of Improved Varieties of Cicerarietinum - Singhai, Benu; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
Seeds of promising Cicer arietinum variety viz., JGG-1, JG-218, JG-322, SAKI-93130 and JG-11 were analyzed for their proximate composition, such as moisture, total ash (and its analysis), crude protein, lipids, totoal carbohydrates, reducing sugar and non-reducing sugar, calcium, phosphorus and crude fibre content.